Yeni Eliza's Weaving Dance Choreography at the Sari Bunian Art Studio, Andaleh Baruh Bukik District, Tanah Datar District - Aqilla, Qorri; Herlinda Mansyur (Universitas Negeri Padang, 2023)
This article aims to describe and analyze Yeni Eliza's Weaving Dance Choreography at Sari Bunian Art Studio in Tanah Datar Regency. The type of research used is qualitative research with descriptive methods. The research instrument is the researcher himself by using tools such as stationery and recording devices. The types of data are primary data and secondary data, which are collected through literature study, observation, interviews, and documentation study. Data analysis was carried out with the steps of data collection, data reduction, data presentation and conclusion drawing. The results showed that the process of Yeni Eliza's Tenun Dance Choreography was started from idea discovery, exploration, improvisation, and composition. Weaving dance choreography has form and aspect aspects, where the form aspect is divided into motion, floor design, top design, group composition, dancers, music, costumes and properties. The content aspect consists of ideas and atmosphere. It can be concluded that Tenun Dance has choreographic planning based on facts because Tenun Dance begins with a new idea with traditional movements and then formed into new movements.